Social Entrepreneurship and Corporate Social Responsibility in the Context of a Moral Economy: Dilemma for Developing Countries (Case of Georgia) - Ia Natsvlishvili (Naše gospodarstvo/Our economy, 2018)
This research discusses the role of social entrepreneurship as an important feature of the moral economy, i.e., a socially responsible business practice. Developing countries, e.g., Georgia, a post-Soviet country, differ from those in the West in this aspect. The author aims to identify peculiarities of social entrepreneurship and corporate social responsibility of Georgian businesses. Desk research provides conceptual analysis of the existing quantitative and qualitative studies, based on prominent scientists’ works in economics and entrepreneurship. A “moral economy” understands business activities as “social services.” Social responsibility is a business’s moral framework, suggesting a company’s obligation to generate social benefit. Social entrepreneurship combines the best practices from the nonprofit and for-profit activities to tackle social needs poorly addressed by businesses and governments. Social entrepreneurship is a relatively new phenomenon in post-Soviet countries, where nongovernmental organizations help in solving many social problems, but their efforts are typically insufficient. Entrepreneurs must find a balance between a company’s success, employees’ needs, and environmental and social stability. These three priorities form the foundations of corporate social responsibility. Economic history provides many examples of moral standards driving the stability of a socio-economic system and profitability of companies with macroeconomic and microeconomic positive impacts. Companies operating in Georgia spend their funds on social projects and charity; moreover, such socially oriented activities are sometimes chaotic. Companies need to implement social responsibility projects as part of their business plans. Strengthening corporate social responsibility could thus support development of social entrepreneurship.